Effects of NAA and different nitrogen levels on nutrient uptake by BARI Gom-26 (Triticum aestivum L.) (Journal of the Asiatic Society of Bangladesh, Science, 2016)
An experiment was conducted to evaluate the effects of NAA (0, 25, 50 ppm) at varying nitrogen levels (0, 50, 75, 100 % of the recommended dose) on nitrogen (N), phosphorus (P) and potassium (K) uptake by shoot and root and percentage of total NPK uptake by BARI Gom-26 at flowering and grain filling stage. Application of NAA at varying nitrogen levels had significant effect on P and K uptake by shoot and root at both stages, whereas, the N content of shoot at flowering stage and of root at the grain filling stage were non-significant.At both the stages, K content of root increased following all the treatments. At flowering and grain filling stage, P content of root and shoot increased and decreased due to different treatments. The maximum percentage of total NPK uptake was recorded from K followed by N and P respectively at both stages. In majority cases there was a decreasing trend in percentage uptake of N and P at grain filling stage compared with flowering stagewhereas, the trend was almost reverse in case of K. The N content of grain increased following all the treatments, the maximum being due to 25 ppm NAA in combination with 75 % N-fertilizer. Only decrease in P content of grain was recorded when 25 ppm NAA without any N-fertilizer was applied. In case of K content, 50 ppm NAA without any N-fertilizer resulted the only decrease. The highest nitrogen use efficiency (NUE) by total plant was also recorded from 50 ppm NAA in combination with 50 % N-fertilizer at flowering stage, whereas, from 25 ppm NAA in combination with 75 % N-fertilizer at grain filling stage.J. Asiat. Soc. Bangladesh, Sci. 42(1): 69-76, June 2016